Pengaruh Kemiskinan, Pengangguran dan Inflasi Terhadap Pertumbuhan Ekonomi di Indonesia - Darsono, Darsono; Munir Hidayat, Asep; Tejaarief, Billy; Kenedi, Kenedi; Wulan Agustini, Anti (Forum Kerjasama Pendidikan Tinggi, 2025)
One of the main problems of Indonesia’s economy is the relatively low economic growth, which is often hampered by high levels of poverty, unemployment, and inflation. These conditions pose challenges in maintaining stability while promoting sustainable development. Economic growth is an important indicator in assessing the performance of a country’s development, which is influenced by various macroeconomic factors. This study aims to analyze the effect of poverty, unemployment, and inflation on Indonesia’s economic growth, both in the short run and long run. In addition, this research also identifies the adjustment mechanism through the error correction approach and analyzes the causal relationship among variables. The method used is secondary data analysis with a quantitative correlational approach. The model applied is the Autoregressive Distributed Lag (ARDL) based on time series data for the period 2014–2024, processed using EViews 12. The results show that in the long run, inflation has a negative and significant effect on economic growth, with a coefficient value of –0.421 and t-statistic 3.12 > t-table 2.06 at a 5% significance level. Unemployment also has a negative but insignificant effect with a coefficient of –0.178 (t-statistic 1.44 < t-table), while poverty shows no significant effect with a coefficient of –0.095 (t-statistic 1.12 < t-table). In the short run, no significant effect of the three variables on economic growth is found. The error correction term (ECT) value of –0.639 is significant at the 5% level, indicating an adjustment process toward long-run equilibrium. The Granger causality analysis also indicates a bidirectional relationship between inflation and economic growth. These findings emphasize that inflation is a key variable that must be controlled to maintain economic stability and foster long-term growth. Meanwhile, poverty alleviation and unemployment reduction policies need to be strengthened in order to have a more tangible impact on achieving sustainable economic growth.